Key dimensions and ideological implications of safe motherhood discourse in a rural indigenous community in Mexico - Laucirica, Jorge O (University of Ottawa (Canada), 2011)
Over the decade of 2000, the Mexican government defined maternal health as a political priority and put pressure on key stakeholders to institutionalize pregnancy and childbirth in rural communities with indigenous population, through coercive use of poverty relief programs and surveillance policies involving health staff, community leaders, neighbours and families in close maternal control from pregnancy to newborn care. Safe motherhood campaigns addressed pregnant women and recent mothers, making them responsible for their own health and for the health of their unborns and newborns. As a result, most pregnant women went for prenatal chats and check-ups and a growing proportion turned away from homebirth assisted by traditional birth attendants. However, most also kept combining traditional and biomedical care and many felt safer delivering in their homes. This study was nested within a community-led research effort to narrow the distance between biomedically-oriented government policies and indigenous views and practices of maternal and newborn care, aiming to reduce maternal mortality and morbidity among aboriginal populations, without marginalizing indigenous cultures. I explore the connections and interactions between health risk discourse --the dominant paradigm in contemporary public health communication-, safe motherhood discourse, and indigenous discourses about maternal care in Xochistlahuaca, a rural community in Guerrero State, Mexico. I show how institutions and individuals draw from existing discourses, adopt them, reject them, and reshape them to make meaning according to their own needs, circumstances, and aspirations. I discuss how these interactions explain and affect maternal and perinatal care among the majority Amuzgo population. I also analyze the ideological implications of government and indigenous discourses in a context of unequal power relations. In particular, the study reveals how different sources construe the roles of key stakeholders, such as indigenous women and men, and how indigenous women handle and reshape multiple discursive pressures from government and community sources concerning maternal health and their role in society. I analyze data from government health promotion materials and interviews with health officials, government health staff, and men and women in the communities, using a theoretical and methodological framework based on critical discourse analysis, social semiotics, systemic functional linguistics, and multimodal approaches. The findings reveal "discursive synergies" and contradictions between government safe motherhood discourse and traditional orders of discourse. They also shed light on how people make coherent --and rational- construals of risk blending their own experiences and multiple, often conflicting discourses in an unequal multiethnic environment with competing authority claims. These findings should be of interest to a range of stakeholders working to prevent maternal and perinatal death in intercultural contexts.
Keywords: Language, Modern.; Latin American Studies.; Sociology, Public and Social Welfare.; Native American Studies.